b - Mandela, Adaba (b, 2018)
At the end of this gruelling ritual journey, the elders of the Mandelas' tribe gathered and Ndaba's grandfather was there, as ever, to share his greatest life lessons.From Nelson Mandela, Ndaba learned the spirit of endurance, the triumph of forgiveness, the power of resistance and the beauty of reconciliation.
Keywords: Presidents -- Biography. -- South Africa